2020
DOI: 10.17533/udea.iee.v38n2e13
|View full text |Cite
|
Sign up to set email alerts
|

Face masks vs. COVID-19: a systematic review

Abstract: The coronavirus disease (COVID-19) spread rapidlyaround the world. Two types of approaches have beenapplied to use of face masks as a tool to prevent the spreadthis disease in society. The aim of the systematic reviewwas to assess the effectiveness of face masks against thenovel coronavirus. A literature search was performed usingdifferent databases until April 30, 2020. Search termswere ‘facemasks’, ‘novel coronavirus’, and ‘healthcareworkers’. Five studies were included in the systematicreview. A study state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 7 publications
0
11
0
3
Order By: Relevance
“…Medical masks filter particles larger than 3 µm [ 5 ], while FFP2 masks block particles up to 0.004 µm. Both mask types are therefore suitable not only for preventing the transmission of coronaviruses [ 8 , 9 ] but also for filtering pollen types larger than 5 µm in size. Medical masks and FFP2 masks both offer hospital staff ‘antiviral protection’ of approximately the same magnitude, which should also be useful for local (eye) or inhaled (nose, bronchial) contact with airborne pollen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical masks filter particles larger than 3 µm [ 5 ], while FFP2 masks block particles up to 0.004 µm. Both mask types are therefore suitable not only for preventing the transmission of coronaviruses [ 8 , 9 ] but also for filtering pollen types larger than 5 µm in size. Medical masks and FFP2 masks both offer hospital staff ‘antiviral protection’ of approximately the same magnitude, which should also be useful for local (eye) or inhaled (nose, bronchial) contact with airborne pollen.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that both medical masks and FFP2 masks offer hospital staff ‘antiviral protection’ of approximately the same magnitude was shown in an overview [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the regression model in Qom are consistent with the results of the study of Mandal et al So that in the regression model and co-linearity diagnostics in Qom, the factor of humidity can explain 85% and maximum temperature can explain 94% of the share of effects in predicting the frequency of positive cases' trend. In similar work by Wu et al, increasing temperature and humidity showed a positive effect on reducing the frequency of positive cases of COVID-19 disease, but nevertheless, preventive and control measures have been emphasized in identifying the sources of infection and preventing the spread of virus outbreaks [20,21]. In the present study, the relationship between urban ambient temperature and the frequency of positive cases of coronavirus was investigated through the machine learning and statistical analysis.…”
Section: Discussionmentioning
confidence: 60%
“…The Chinese government quickly proclaimed prevention and control measures for interpersonal communication during the Spring Festival, especially the use of face masks, to impede transmission in health care and community settings ( 12 ). In the year 2020, the Chinese government strongly advocated the universal use of face masks in public places as a means of source control during the COVID-19 pandemic ( 13 ). Chinese residents generally supported the use of masks in public places ( 14 ) as a supplement to social distancing and hand hygiene to contain or slow the exponential growth of the epidemic ( 15 ).…”
Section: Introductionmentioning
confidence: 99%